2010
DOI: 10.1159/000317523
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Multilocular Cystic Renal Cell Carcinoma and Leiomyoma in the Same Kidney: Previously Unreported Association

Abstract: We present an unusual case of concurrent occurrence of a multilocular cystic renal cell carcinoma and a leiomyoma in the same kidney of a patient with no evident clinical symptoms. A 38-year-old man was found incidentally to have a cystic right renal mass on computed tomography. Laparoscopic radical nephrectomy was performed under a preoperative diagnosis of cystic renal cell carcinoma. Histology revealed a multilocular cystic renal cell carcinoma and a leiomyoma. This is the first report of this kind of prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Although most RCCs originate from proximal tubules, a detailed immunohistochemical study performed by Imura et al has shown that MCRCC originates from distal tubules [8]. However, MCRCC's pathology still has not been completely illuminated [9]. In our case, as well, we observed that the tumor was surrounded by a fibrous capsule, and that it consisted of cysts that were divided by septas containing clear cell groups, and that the solid component was 2%.…”
Section: Discussionsupporting
confidence: 54%
“…Although most RCCs originate from proximal tubules, a detailed immunohistochemical study performed by Imura et al has shown that MCRCC originates from distal tubules [8]. However, MCRCC's pathology still has not been completely illuminated [9]. In our case, as well, we observed that the tumor was surrounded by a fibrous capsule, and that it consisted of cysts that were divided by septas containing clear cell groups, and that the solid component was 2%.…”
Section: Discussionsupporting
confidence: 54%
“…7 Macroscopically, the leiomyoma appears as a solid tumor, with elastic consistency because it is made up of muscle and collagen, well defined, with a fascicular appearance and a pearly-white, gray-white or reddish color when cut, depending on the vascularization; can be covered by ulcerated or non-ulcerated mucosa. 8 Histologically, they are made up of mature smooth muscle cells with abundant eosinophilic cytoplasm, organized in interlaced bundles devoid of atypia and necrosis, and with mild mitotic activity (<1 mitosis/50 high-power fields). 9 The differential diagnosis includes other vaginal tumors, such as: Gartner, Bartholino or Skene gland cysts, urethral diverticula, urethrocele, cystocele, rectocele and neurofibromas.…”
Section: Discussionmentioning
confidence: 99%